Quality/Quantity Changes in Oil and Morphological Traits of Medicinal Pumpkin (Cucurbita pepo L.) under Different Cultivation Practices - MR Labbafi; I Allahdadi; GHA Akbari; F Najafi; H Khalaj; A Mehrafarin (Institue of Medicinal Plants, ACECR, 2012)
Background: Medical pumpkin is a medicinal plant that has a special place in the pharmaceutical industry, and evaluation of quantitative and qualitative yield is a under different agronomic treatments is necessary. Objective: Investigating of quality/quantities yield of oil and morphological traits of Cucurbita   pepo. affected of planting date and row arrangement.   Methods: This study was done as split plot on complete randomized blocks design with 3 replications at Research field of Aburaihan College, University of Tehran in 2010 and 2011 years. Treatments were included 3 main plots of planting dates (20 Apr, 21 May and 21 June) and 3 subplots of row arrangement (1, 1.5 and 2 meter between two rows). In this study evaluated 1000 seeds weight, seeds number in fruit, seeds weight per fruit, seed yield, seed produce index, oil percentage and oil yield. Results: The year had not significant effect on any traits expect of oil percentage and seeds number in fruit. The interaction of planting date and row arrangement were significant in all quality and quantity traits. Maximum of seed yield, seed oil percent and oil yield were obtained in 1 meter row spacing21 may treatment and 1.5 meter21 June treatment. Maximum of unsaturated fatty acids percent and minimum of saturated fatty acids percent were obtained in planting date of June with 1.5 and 2 meter row spacing. Conclusion: According to significant effect of row arrangement and planting date on seed and oil yield of medical pumpkin, quality and quantity growth followed economic yield of this plant could be improved by using appropriate agronomic management.